Method of Moment Thin Wire Computer Program Comparison for Complex Structures and Coarse Accuracy - Perini, J.; Schuman, H. K. (3rd Symposium and Technical Exhibition on Electromagnetic Compatibility, Rotterdam, 1979)
Three typical thin-wire moment method computer programs OS (sinusoidal Galerkin) SYR (triangle Galerkin), and WRSMOM (pulse expansion-impulse weighting) are compared. They are applied to four antenna models - two simple and two complex. The complex models are representative of shipboard "twin fan" antennas. The primary purpose is to determine if a "best" computer program exists given "coarse" accuracy (within ∼3 dB of converged results) as acceptable in predicting the driving point impedances and farfield radiation patterns exhibited by such structures